From visual journalism to informative experiences: our research on socio design artefacts in the information field - Moretti, Matteo (img journal, 2019)
This paper introduces the design-research work in the field of information design developed by the author, as a member of the Trans-form research cluster at the Free University of Bozen-Bolzano. The Trans-form group focuses on the interdisciplinary research studies and practices that combine design and the social sciences to promote the concept of sustainability across diverse fields, such as economics, politics, and finally information, with the goal of achieving an inclusive and aware society. Specifically, the way information is produced, consumed, and processed today, online and offline, offers an important space to design interventions and make an impact on society: an aspect to which this paper contributes, presenting the research done by the author in collaboration with sociologists, anthropologists, and journalists over the past five years at the Trans-form cluster. The following essay introduces the theoretical framework of socio-design within which the Trans-form cluster operates, and then focuses on socio-design in the information field. It subsequently moves on to the research conducted by Trans-form on information socio- artefacts, introducing three of the most significant case studies, which challenged a broader audience with engaging informative experiences aimed at raising awareness to foster possible behavioural change. Finally, the conclusion highlights the research findings over five years and points to new possibilities to design and impact society through socio-design research.